ROLE JUST IN TIME METHOD FOR EFFORTS TO ELIMINATE NON-VALUE ADDED ACTIVITY IN PRODUCTION GARMENT COMPANY VOXI 73 - Kantjai, Silvana; Pandowo, Merinda (Universitas Sam Ratulangi, 2015)
The concept of cost effectiveness or known as the manufacturing cycle effectiveness (MCE) is the ratio between the processing time to the cycle time.This research is to identify the extent to which the benefits and role of Just In Time (JIT) Method for eliminating all activities or resources that are not value-added and to give an idea of ​​the importance of the implementation of Just In Time for companies to improve efficiency and productivity. This research using a Garment Company